Small-area Fingerprint Recognition Based on Improved ORB Algorithm in Embedded Environment - Xiao, Jianyu; Liu, Jiuan; Liu, Huanhua (EAI Endorsed Transactions on Internet of Things, 2022)
Most of the fingerprint matching algorithms were proposed for large area fingerprints, which can hardly work effectively in small-area fingerprints. In this work, an improved ORB algorithm is proposed for small-area fingerprint matching in embedded mobile devices. In feature descriptor design, we analyzed the characters of the fingerprint in the embedded mobile devices and discard the multi-scale feature process to reduce the amount of operations. Moreover, we proposed a fusion descriptor combing LBP and rBRIEF descriptor. In the key point matching process, we proposed a two-step (coarse and fine) matching method by using Hamming distance and cosine similarity, respectively. The experimental results show that the proposed method has a rejection rate of 6.4%, a false recognition rate of 0.1%, and an average matching time of 58ms. It can effectively improve the performance of small-area fingerprint matching and meet the application requirements of embedded mobile device authentication.
Keywords: Fingerprint recognition; Internet of thing; ORB; Feature point extraction and matching; Feature fusion